The therapeutic potential of different mesenchymal stem cells and their derived exosomes in metabolic dysfunction-associated steatotic liver disease - Qin, Dan; Huang, Pingping; Chen, Jialing; Wu, Changjun; Liang, Yuzhen (Frontiers in Endocrinology, 2025)
Metabolic dysfunction-associated steatotic liver disease is a metabolic disease with an increasing incidence. Its pathogenesis involves the interaction of multiple factors. There is currently no specific treatment, so early prevention and treatment are crucial. Mesenchymal stem cells are a type of cell with the ability to self-renew and differentiate in multiple directions. They have a wide range of sources, including umbilical cords, bone marrow, and fat, and have various biological functions such as anti-inflammation, immune regulation, anti-oxidation, and inhibition of fibrosis. They have shown significant potential in the treatment of non-alcoholic fatty liver disease. In recent years, mesenchymal stem cells derived exosomes have been shown to be rich in bioactive substances, and to be involved in intercellular communication, regulating metabolism, reducing inflammatory responses, improving lipid metabolism, inhibiting fibrosis, and other processes that contribute to the treatment of metabolic dysfunction-associated steatotic liver disease. Mesenchymal stem cells and mesenchymal stem cell-derived exosomes play an important role in the pathogenesis and treatment of metabolic dysfunction-associated steatotic liver disease and provide new potential and direction for the treatment of Metabolic dysfunction-associated steatotic liver disease. This article reviews the role and effects of mesenchymal stem cells and mesenchymal stem cell-derived exosomes from different sources in Metabolic dysfunction-associated steatotic liver disease and discusses their prospects as potential therapeutic strategies.